Superstructure Optimization of Dimethyl Ether Process - Erturk, Emrullah; Aydin, Erdal; Sarrafi, Sahin; Deliismail, Ozgun; Zahidova, Aysel; Sildir, Hasan (Elsevier B.V., 2022)
Integration of process flowsheet simulators and optimization algorithms is a prominent approach to address simultaneous design and optimization of processes, which is represented by a mixed integer nonlinear programming (MINLP) formulation. In this study, DWSIM, a free and rarely used simulator, is used as a black-box function for the evaluation in genetic algorithm in MATLAB. Proposed approach is implemented to a dimethyl ether process, calculating optimum processing conditions in addition to structural decision variables including the feedstock type, reactor, and separation unit selections. Results show that syngas has the major impact on the process economics and is significantly more economical feedstock although high number of additional processing units are required. © 2022 Elsevier B.V., All rights reserved.
Keywords: black-box optimization; dimethyl ether process; DWSIM; mixed integer nonlinear programming; process synthesis; superstructure optimization